Exosomes Derived From Pancreatic Stellate Cells: MicroRNA Signature and Effects on Pancreatic Cancer Cells. Issue 1 (January 2017) - Takikawa, Tetsuya; Masamune, Atsushi; Yoshida, Naoki; Hamada, Shin; Kogure, Takayuki; Shimosegawa, Tooru
Abstract : Objectives: Pancreatic stellate cells (PSCs) interact with pancreatic cancer cells in the tumor microenvironment. Cell constituents including microRNAs may be exported from cells within membranous nanovesicles termed exosomes. Exosomes might play a pivotal role in intercellular communication. This study aimed to clarify the microRNA signature of PSC-derived exosomes and their effects on pancreatic cancer cells. Methods: Exosomes were prepared from the conditioned medium of immortalized human PSCs. MicroRNAs were prepared from the exosomes and their source PSCs, and the microRNA expression profiles were compared by microarray. The effects of PSC-derived exosomes on proliferation, migration, and the mRNA expression profiles were examined in pancreatic cancer cells. Results: Pancreatic stellate cell–derived exosomes contained a variety of microRNAs including miR-21-5p. Several microRNAs such as miR-451a were enriched in exosomes compared to their source PSCs. Pancreatic stellate cell–derived exosomes stimulated the proliferation, migration and expression of mRNAs for chemokine (C - X - C motif) ligands 1 and 2 in pancreatic cancer cells. The stimulation of proliferation, migration, and chemokine gene expression by the conditioned medium of PSCs was suppressed by GW4869, an exosome inhibitor. Conclusions: We clarified the microRNA expression profile in PSC-derived exosomes. Pancreatic stellate cell–derived exosomes might play a role in the interactions between PSCs and pancreatic cancer cells. Abstract : Supplemental digital content is available in the text.